The new capitalist philanthropy and the intensification of the teacher's work: reflections on corporate volunteering - Maria Vieira Silva; Aline Barbosa de Miranda; Paulo Vinicius Lamana Diniz (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
This paper summarizes research results obtained by the authors on the new formats of capitalist philanthropy through volunteering work. It highlights, especially,teaching practices developed in companies with "social responsibility", consolidating a new modality of teacher's work. From speeches of company managers and volunteer teachers, the analyses contextualize the paradoxes, contradictions, and ambiguities found in volunteering activities, catching the processes of work intensification observed in the set of devices provided by the capitalist administration, which focus on the subjective dimensions of the worker and the objective dimensions of capital accumulation.